PENGEMBANGAN PEMBIBITAN DAN PENGELOLAAN KEBUN KOPI, KARET SERTA SAWIT BERSERTIFIKAT DI DESA KOTANIUR BENGKULU - Priyono Prawito; Agus Iswanrijanto; Sumarto Widiyono (DHARMA RAFLESIA, 2017)
ABSTRACTMost of Kota Niur population is farmer, consisting more than 90% of the population. The three most important of cultivated plants are coffee, rubber, and palm oil, cultivated intraditional system, with relatively low productivity. The purposes of these projects aretraining the farmers to prepare a good seedling for their plantation, and practicing a goodmanagement for their farm. This project has been conducted since May to the December2013 by establishing 3000 plants of coffee seedling, 11000 plants ofrubber seedling, and2000 plants of oil palm seedling. Demonstration plots have also been developed for coffee,rubber and oil palm plantations. One-hectare demo plots for coffee, two locations of onehectaredemoplots for rubber, and two locations of one-hectaredemo plots for oil palmplantations. Nursery area of about 1000 m2has also been established with fence,irrigation, and shading facilities. Training of grafting, occultation, and nursery have alsobeen conducted to prepare for coffee, rubber, and oil palmnursery, resulting in threegroups of 5-people well trained in coffee grafting, rubber oculation and oilpalm nursery. Agricultural extension for farm management has also been conducted especially for coffee,rubber, and oil palm plantation management. Keywords: coffee, grafting, occultation, oil palm, rubber